The Element ideal graph Γ(pα qβ ) (Z) - Abdul-Qadr, Fryad H. (Sulaimani Journal for Pure and Applied Sciences, 2006)
Let R be acommutative ring with identity and let x be an element of R. The Element Ideal Graph Γx (R) is a graph whose vertex set is the set of non-trivial ideals of R and two distinct ideal vertices I and J are adjacent if and only if x∈I J. In this paper we investigate the element ideal graph Γ(pα qβ ) (Z) to explore some of its properties with providing some examples, where Z is the set of integers, α, β∈Z+ and p and q are distinct prime numbers.
Keywords: Element Ideal Graph; Clique; Diameter